Characterization of biogenic volatile organic compounds and their oxidation products in a stressed spruce-dominated forest close to a biogas power plant - J. Song; J. Song; G. I. Gkatzelis; R. Tillmann; N. Brüggemann; T. Leisner; H. Saathoff (Atmospheric Chemistry and Physics)
Biogenic volatile organic compounds (BVOCs) are key components of the atmosphere, playing a significant role in the formation of organic aerosols (OAs). However, only a few studies have simultaneously examined the characteristics of BVOCs and OAs in forest ecosystems on the background of environmental stressors, such as consecutive droughts and extensive bark beetle infestations. Here, we present real-time measurements of OAs and BVOCs in a stressed spruce-dominated forest near a biogas power plant (BPP) in western Germany during June 2020. A proton-transfer-reaction time-of-flight mass spectrometer coupled with a particle inlet (CHARON-PTR-ToF-MS) and a Vocus-PTR-ToF-MS were used to measure OAs and BVOCs. The average OA mass concentration was 0.8 ± 0.5 µg m−3, consisting mainly of semi-volatile monoterpene oxidation products. The average mixing ratios of isoprene (0.58 ± 0.54 ppb) and monoterpenes (2.5 ± 5.3 ppb) were higher than the values previously measured in both German temperate forests and boreal forests. Based on a wind direction analysis, BVOC data were categorized into two groups: one mainly influenced by biogenic emissions from an intact forest and a clear-cut area (referred to as the biogenic group) and the other mainly influenced by anthropogenic emissions from a BPP and a village (referred to as the anthropogenic group). High mixing ratios of monoterpenes were observed in the anthropogenic group, indicating a significant contribution of BPP emissions. In the biogenic group, the variations in BVOC mixing ratios were driven by the interplay between meteorology, biogenic emissions and their photochemical consumption. Positive matrix factorization analysis of VOCs revealed substantial contributions of oxygenated organic compounds from the photochemical oxidation of BVOCs during daytime, while monoterpenes and their weakly oxidized products dominated at night. Furthermore, increasing relative humidity and decreasing temperatures promoted the gas-to-particle partitioning of these weakly oxidized monoterpene products, leading to an increase in nighttime OA mass. The results demonstrate that variations in BVOCs are influenced not only by meteorological conditions and biogenic emissions but also by local BPP emissions and subsequent chemical transformation processes. This study highlights the need to investigate the changes in biogenic emissions in stressed European forests.